SDL Index Predicts Stroke-Associated Pneumonia in Patients After Endovascular Therapy - Zhang, Bowei; Zhao, Wenbo; Wu, Chuanjie; Wu, Longfei; Hou, Chengbei; Klomparens, Kara; Ding, Yuchuan; Li, Chuanhui; Chen, Jian; Duan, Jiangang; Zhang, Yunzhou; Chang, Hong; et al. (Frontiers in Neurology, 2021)
Objective: This study aimed to develop and validate a novel index to predict SAP for AIS patients who underwent endovascular treatment. Methods: A study was conducted in an advanced comprehensive stroke center from January 2013 to December 2019 aiming to develop and validate a novel index to predict SAP for AIS patients who underwent endovascular treatment. This cohort consisted of a total of 407 consecutively registered AIS patients who underwent endovascular therapy, which was divided into derivation and validation cohorts. Multiple blood parameters as well as demographic features, vascular risk factors and clinical features were carefully evaluated in the derivation cohort. The independent predictors were obtained using multivariable logistic regression. The scoring system was generated based on the β-coefficients of each independent risk factor. Results: Ultimately, a novel predictive model: the SDL index (stroke history, dysphagia, lymphocyte count less than 1.00×103/μL) was developed. The SDL index showed good discrimination both in the derivation cohort (AUROC: 0.739, 95% confidence interval, 0.678-0.801) and the validation cohort (AUROC: 0.783, 95% confidence interval, 0.707-0.859). The SDL index was well calibrated (Hosmer- Lemeshow test) in the derivation cohort (P=0.389) and the validation cohort (P=0.692). We therefore divided our population into low (SDL index=0), medium (SDL index=1) and high (SDL index≥2) risk groups for SAP. The SDL index showed good discrimination when compared with 2 existing SAP prediction models. Conclusions: The SDL index is a novel feasible tool to predict SAP risk in acute ischemic stroke patients post endovascular treatment.